Decarbonylation through Aldehydic C–H Bond Cleavage by a Cationic Iridium Catalyst - Shirai, Tomohiko; Sugimoto, Kazuki; Iwasaki, Masaya; Sumida, Ryuki; Fujita, Harunori; Yamamoto, Yasunori (Synlett, 2019)
We report the decarbonylation of aldehydes through an aldehydic C–H bond cleavage catalyzed by a cationic iridium/bisphosphine catalyst. The reaction proceeds under relatively mild conditions to give the corresponding hydrocarbon products in moderate to high yields. In addition, this cationic iridium catalyst system can be applied to an asymmetric hydroacylation of ketones.
Keywords: decarbonylation; iridium catalysis; aldehydes; C–H bond cleavage; asymmetric catalysis; hydroacylation